On the use of displaced river terraces to characterize active tectonics of the Zagros orogenic belt, SW Iran - Iman Nezamzadeh; Ali Faghih; Behnam Oveisi; Timothy Kusky; Narges Khajavi; Masoumeh Soleimani; Jiannan Meng (Results in Earth Sciences)
Investigating fault deformation in Late-Quaternary sediments provide valuable data to seismic hazard analysis especially relevant for the urban areas. Integration of displacement of geomorphic markers and ages of Quaternary sediment is needed to measure deformation rates accurately. In order to produce data on intermediate-term deformation rates along the Sabzpoushan Fault Zone (SFZ) situated in the Zagros Mountains of south-west Iran, the optically stimulated luminescence (OSL) dating technique was applied to the tectonically influenced terraces of the Mianrod River passing through the fault zone. Field evidence and satellite imagery revealed that geomorphic markers include strike-slip displacement of terraces, different levels of the fluvial markers, shifting in Bakhtiary Formation, fast change in trend of the river and expansion of erosional gully, deformed horizontally along the Fault Zone. These geomorphic indices suggest that Mianrod River deflected along the SFZ as a consequence of faulting during multiple faulting cycles. The OSL dates obtained from the study area indicate that strike-slip deformation rate along the Sabzpoushan Fault Zone is 1–2.8 ± 0.2 mm y−1 (for ∼100 ka). It is suggestive from the research that a significant part of this estimated rate of deformation results from aseismic crustal deformation, but the areas with the highest likelihood of the Sabzpoushan near-surface deformation, as well as the west parts of the city of Shiraz, should be considered as high seismic hazard areas.